STRUCTURAL MODIFICATION OF POLYPROPYLENE AND PROPERTIES OF THE RESULTING MATERIALS (Journal of Universal Science Research, 2025)
The article deals with polymeric materials widely used in industry and other spheres of social life, their structural modification, chemical and physical properties depending on the type of polymer matrices and fillers. Polymer composites can have optimal physicochemical parameters and lower cost than traditional composites. The paper describes the properties of polypropylene blends in this field.